2015
DOI: 10.1016/j.bmcl.2015.08.054
|View full text |Cite
|
Sign up to set email alerts
|

New class of 8-aryl-7-deazaguanine cell permeable fluorescent probes

Abstract: A one step synthesis of fluorescent 8-aryl-(7-deazaguanines) has been accomplished. Probes exhibit blue to green high quantum yield fluorescence in a variety of organic and aqueous solutions, high extinction coefficients, and large Stokes shifts often above 100 nm. The probes are highly cell permeable, and exhibit stable bright fluorescence once intracellular; therefore are suited to the design of biosensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…One fruitful design strategy for fluorescent analogues of the purine bases adenine and guanine has been to substitute these molecules at position C8 with conjugating groups, , leading, among others, to the subject of the present study: 8-vinylguanine (8vG), whose structure is shown in Figure . The FBA 8vG was synthesized by Nadler and co-workers as an isomorphic fluorescent analogue of guanine, and it was reported to combine several properties that are favorable for application in studies of DNA structure. , The replacement of guanine with 8vG in double-stranded DNA results in only a minor destabilization of the duplex .…”
Section: Introductionmentioning
confidence: 99%
“…One fruitful design strategy for fluorescent analogues of the purine bases adenine and guanine has been to substitute these molecules at position C8 with conjugating groups, , leading, among others, to the subject of the present study: 8-vinylguanine (8vG), whose structure is shown in Figure . The FBA 8vG was synthesized by Nadler and co-workers as an isomorphic fluorescent analogue of guanine, and it was reported to combine several properties that are favorable for application in studies of DNA structure. , The replacement of guanine with 8vG in double-stranded DNA results in only a minor destabilization of the duplex .…”
Section: Introductionmentioning
confidence: 99%
“…While P1 and P4 can be obtained commercially, P2 , P3 , P5 , and P6 were prepared in-house. P2 and P3 were synthesized according to a literature procedure, with analytical data consistent with that reported previously. The synthesis of P5 and P6 began with Friedel–Crafts acylation of fluoranthene using acetyl chloride and AlCl 3 in dry dichloromethane (DCM) under Schlenk conditions, to afford both the 3-acetyl ( 1 ) and 8-acetyl ( 2 ) fluoranthene derivatives . Because of the chemical similarity of the two products, separation was performed by column chromatography using very fine grade silica (10–14 μm, LC35A Davisil, Grace Davison) to fully resolve the products.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Dhimitruka et al synthesized the base 8-phenyl-7-deazaguanine 21, which shows fluorescence. 29 However, it was observed that compound 21 only develops strong fluorescence in aprotic polar solvents, for instance in DMSO (Φ = 0.96), whereas fluorescence decreases strongly in aqueous medium (Φ = 0.12).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Next, fluorescence measurements were performed in DMSO (Figure 2a). The fluorescence intensity of nucleoside 2 (Φ = 0.81) is slightly lower compared to that of nucleobase 21 (Φ = 0.96), 29 whereas other nucleosides (1, 3, and 4) are almost nonfluorescent.…”
Section: The Journal Of Organic Chemistrymentioning
confidence: 86%